Assessing Wave Attenuation With Rising Sea Levels for Sustainable Oyster Reef-Based Living Shorelines - Salatin, Reza; Wang, Hongqing; Chen, Qin; Zhu, Ling (Frontiers in Built Environment, 2022)
In densely populated coastal areas with sea-level rise (SLR), protecting the shorelines against erosion due to wave impact is crucial. Along with many engineered structures like seawalls and breakwaters, there are also green structures like constructed oyster reefs (COR) that can not only attenuate the incident waves but also grow and keep pace with SLR. However, there is a lack of data and understanding of the long-term wave attenuation capacity of the living shoreline structures under SLR. In this study, we used the phase resolving Boussinesq model, FUNWAVE-TVD, to examine the hydrodynamics including wave height and wave-induced currents around the COR in Gandy’s Beach living shoreline project area in the upper Delaware Bay, USA. Waves were measured at six locations (offshore to onshore, with and without the COR) in the Gandy’s Beach living shoreline project area for two winter months, during which four Nor’easters occurred. We selected three cases that represent prevailing wind, wave, and tide conditions to examine the fine spatial and temporal changes in wave height and current velocity by the construction of the reefs. Wave heights and wave energy spectra generated from FUNWAVE-TVD were then validated with field observations. It is found that FUNWAVE-TVD is capable of simulating waves and associated hydrodynamic processes that interact with the COR. Model results show that wave attenuation rates vary with the incident wave properties and water depth, and wave-induced circulation pattern is affected by the COR. The wave attenuation capacity of COR over the next 100 years was simulated with the incorporation of the oyster reef optimal growth zone. Our study found that sustainable wave attenuation capacity can only be achieved when suitable habitat for COR is provided, thus it can vertically grow with SLR. Suitable habitat includes optimal intertidal inundation duration, current velocity for larval transport and settlement, on-reef oyster survival and growth, and other environmental conditions including salinity, temperature, and nutrient availability. Furthermore, model results suggest that it would take COR approximately nine years after construction to reach and maintain the maximum wave attenuation capacity in sustainable living shorelines.